(untitled) (Medical Forum Monthly, 2021)
Objective: Comparison of Spirometric changes in workers of New Subzi Mandi Karachi with control. It was also consisting on Air sampling for detection of Microorganisms in subzi mandi & control area. Study Design: Case control study Place and Duration of Study: This study was conducted at the new Subzi Mandi Karachi & control area, more than 5 kms from Subzi mandi from August 2019 till Jan 2020 for a period of five months. Materials and Methods: 100 controls of similar age & socioeconomic strata were included. Known COPD & asthma & cardiovascular disease were excluded. Chi square and independent t-test was applied. Four different media used to collect ambient organisms, allowed to proliferate on kits & detected in microbiology lab. Results: Bacteria & fungi detected by us were more concentrated in Subzi mandi. From 245 individuals 145 cases while 100 controls. Smokeless tobacco abusers were found significant association in cases. Height was again found more in cases. The mean of spirometric parameters provided clues of present article & only Predicted FVC% has significant association between groups. Conclusion: Bio-aerosol & smokeless tobacco abuse causes subtle changes on modern routine spirometry. Clue found subtle because workers were tall & had optimum BMI. Spirometric results of controls were far behind from ideal value of adult male because they had significantly raised association of smoking